Oral History Program Interview Terry Bennett Clipper - Clipper, Terry Bennett
Clipper was born in Dustin, Hughes County, Oklahoma in 1917. He came to Los Angeles, California in 1938 working on orange groves, and moved to Bakersfield on June 9, 1948 working on cotton and grape crops. His interview includes describing what the WPA and CCC did for people during the Great Depression, people's rejection to relief, issues of race relations between farmworkers and growers, successful strikes and labor organization, description of ditch camps, why "Okie" was a derogatory term, that The Grapes of Wrath did a good job portraying the migrants, and bootleggers.